Allergy‐related diseases and recurrent abdominal pain during childhood – a birth cohort study. Issue 11 (1st October 2014) - Olén, O.; Neuman, Å.; Koopmann, B.; Ludvigsson, J. F.; Ballardini, N.; Westman, M.; Melén, E.; Kull, I.; Simrén, M.; Bergström, A.
Summary Background Allergy and immune dysregulation may have a role in the pathophysiology of recurrent abdominal pain of functional origin, but previous studies of allergy‐related diseases and abdominal pain have contradictory results. Aim To examine the association between allergy‐related diseases or sensitisation during childhood and abdominal pain at age 12 years. Methods In this birth cohort study of 4089 children, parents answered questionnaires regarding asthma, allergic rhinitis, eczema and food hypersensitivity ('allergy‐related diseases') at ages 0, 1, 2, 4, 8 and 12 years. Blood for analyses of allergen‐specific IgE was sampled at 4 and 8 years. At 12 years, the children answered questions regarding abdominal pain. Children with coeliac disease or inflammatory bowel disease were excluded. Associations were examined using multivariable logistic regression. Results Among 2610 children with complete follow‐up, 9% (n = 237) reported abdominal pain at 12 years. All allergy‐related diseases were associated with concurrent abdominal pain at 12 years and the risk increased with increasing number of allergy‐related diseases (P for trend <0.001). Asthma at 1 and 2 years and food hypersensitivity at 8 years were significantly associated with abdominal pain at 12 years. There was an increased risk of abdominal pain at 12 years in children sensitised to food allergens at 4 or 8 years, but in stratified analyses, this was confined to children whose parents had not reported food hypersensitivity at time of sensitisation. Conclusion Allergy‐related diseases as well as sensitisation to food allergens were associated with an elevated risk of abdominal pain, and the risk increased with the number of allergy‐related diseases.